Aktywność ekonomiczna ludności : klasyfikacja osób za pomocą wielomianowych modeli logitowych oraz jej związek z modelami hazardu dla czasów trwania - Landmesser, Joanna Małgorzata (Economic Activity of People : Classification Using Multinomial Logit Models and Their Connection with Hazard Models, 2008)
In this paper the usage of a multinomial logit model MLM for the estimation of a discrete time competing risks hazard models is described. The MLM model provides a close approximation to a hazard model for interval-censored data for which the hazard rate is constant within each interval. The usefulness of the information provided by the MLM model for predicting a categorical outcome variable reflects a quality of the prior hazard model. To illustrate this statement we use employment duration data from the Labour Force Survey in Poland (BAEL).
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 426-434